Biomonitoring of chlorophenols in human urine from several Asian countries, Greece and the United States. (January 2018) - Honda, Masato; Kannan, Kurunthachalam
Abstract: Chlorophenols (CPs) are used in the production of pesticides and preservatives. Although human exposure to CPs has been known for years, current exposure levels to these chemicals in Asian countries are not known. In this study, we analyzed concentrations of eight CPs in 300 human urine samples collected from nine countries. Of these CPs, 2, 5-dichlorophenol and 2, 4-dichlorophenol were found at the highest median concentrations (median for all nine countries: 1.78 and 0.34 ng/mL, respectively). Pentachlorophenol was found in 59% of the samples analyzed at a median concentration of 0.07 ng/mL. Urine samples from Japan had the highest concentration of total CPs (median: 16.7 ng/mL) with 2, 5-dichlorophenol accounting for 93.1% of the total concentration. The estimated daily intake (DI) for precursors of dichlorophenols varied widely, but several samples showed values higher than the acceptable DI recommended by the United States Environmental Protection Agency (EPA). These results suggest that CP exposure, especially to dichlorophenols, is prevalent in several countries, particularly in Asia, suggesting a pressing need for further assessment of the global sources and potential health effects of these chemicals. Graphical abstract: Highlights: Eight chlorophenols were analyzed in 300 human urine from nine countries. Dichlorophenols were found at the highest concentrations and frequency. Estimation of daily intake for dichlorophenols in several samples exceeded the RfD. Abstract : Chlorophenol exposures in populations in Asian countries continue to be a concern.